DIPLOMASI MARITIM INDONESIA TERHADAP HACGAM (HEAD OF ASIAN COAST GUARD AGENCY MEETING) DALAM MEWUJUDKAN INDONESIA POROS MARITIM DUNIA PADA TAHUN 2016-2017 - Maudy Dwi Ramadhanti; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Making Indonesia the worldʹs maritime axis is the vision promoted by Joko Widodo (Jokowi) to the next five years of his tenure after his victory in the   residential election 2014. This goal is in line with the struggle of Sukarno, who wanted Indonesia to become a strong and independent maritime country at the  ime. Hisdesire was rooted from the awareness of Indonesia’s strategic position aswell as maritime potentials that the country have. The main objective of Jokowi’s idea is to boost Indonesiaʹs economic growth and equitable development which is focused on the marine sector. This research was prepared using the perspective of Neorealism, the theory of diplomacy and the concept of maritime security. This research was arranged using descriptive analysis with qualitative approach. Supporting data is obtained through  document, and literature study. This research was arranged using descriptive analysis with qualitative approach. Supporting data is obtained through interviews, document, and literature study. The result shows that the defense diplomacy’s instrument was built upon series of international cooperation and the development of state’s defense posture itself. Therewith, Indonesian government undertakes the defense diplomacy efforts by playing an active role in forum regional level such as HACGAM.  These two aspects eventually have a prime significance in shaping Indonesia as the Global Maritime Fulcrum, especially in the achievement of defense, security, law enforcement, and marine safety.Key Words: HACGAM, World Maritime Axis, Defence Diplomacy.